2022
DOI: 10.7717/peerj.13589
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis of the serratus anterior and upper trapezius in closed kinetic chain exercises performed on different unstable support surfaces: a systematic review and meta-analysis

Abstract: Background Multiple investigations have compared the electromyographic (EMG) activity of the scapular muscles between stable and unstable support surfaces during the execution of closed kinetic chain exercises. However, these comparative analyses have grouped different unstable surfaces (wobble board, BOSU, therapeutic ball, and suspension equipment) into a single data pool, without considering the possible differences in neuromuscular demand induced by each unstable support surface. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…It is difficult to discuss the findings for the other muscles evaluated, since there are few studies, and none of them had quantitative data. The results of the present study contribute to understanding the effect of adding unstable surfaces on the agonist muscles since systematic reviews have focused on the role of the stabilizer muscles [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to discuss the findings for the other muscles evaluated, since there are few studies, and none of them had quantitative data. The results of the present study contribute to understanding the effect of adding unstable surfaces on the agonist muscles since systematic reviews have focused on the role of the stabilizer muscles [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two systematic reviews have compared the effects of using unstable surfaces on electromyographic activity, and both only evaluated periscapular muscles [ 21 , 22 ]. The first study included 33 studies that evaluated 678 subjects and showed that using unstable surfaces generated a slight increase in upper trapezius activity and a slight decrease in serratus anterior activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[9][10][11] This impairment of neuromuscular control has been widely detected by surface electromyographic (sEMG) amplitude of the scapular stabilizing muscle (serratus anterior [SA], middle trapezius [MT], lower trapezius [LT], and upper trapezius [UT]), through certain criteria such as low activation amplitude, muscle imbalance (i.e., altered activation ratio), and delayed onset latency. 1,4,9,12 Thus, sEMG amplitude values ≥50% maximum voluntary isometric contraction (MVIC) are categorized as optimal for activation of the scapular stabilizing muscle, facilitating the interpretation of sEMG amplitude in research and clinical practice. 8 Furthermore, optimal muscle balance has been investigated using the activation ratio, that is, the relative activity of one muscle versus another rather than the absolute value of sEMG amplitude.…”
mentioning
confidence: 99%
“…Altered scapular position and movement is often caused by an imbalance of agonist and antagonist muscles, either by inhibition or overactivity of the scapular muscles 5,9–11 . This impairment of neuromuscular control has been widely detected by surface electromyographic (sEMG) amplitude of the scapular stabilizing muscle (serratus anterior [SA], middle trapezius [MT], lower trapezius [LT], and upper trapezius [UT]), through certain criteria such as low activation amplitude, muscle imbalance (i.e., altered activation ratio), and delayed onset latency 1,4,9,12 . Thus, sEMG amplitude values ≥50% maximum voluntary isometric contraction (MVIC) are categorized as optimal for activation of the scapular stabilizing muscle, facilitating the interpretation of sEMG amplitude in research and clinical practice 8 .…”
mentioning
confidence: 99%